Sustainable waste management challenges in developing countries - Pariatamby, Agamuthu; Shahul Hamid, Fauziah; Bhatti, Mehran Sanam (IGI Global, 2020)
"This book examines waste management practices in developing countries such as waste generation and waste composition. It also explores the roadblocks and potential opportunities involved in achieving integrated waste management in developing countries"--